The Effect of Using Capcut Media on The Science Learning Outcomes of Smp Negeri 1 Maiwa - Nisma, Nisma; M, Usman; Hasanuddin, Hasanuddin; Hermansyah, Sam (Journal International Inspire Education Technology, 2024)
In order to determine the impact of employing Capcuit media on scientific learning outcomes for class VII students at SMP Negeri 1 Maiwa Regency of Enrekang patent, this study employs quantitative ideation and experimental research kinds. The research population consisted of all class VII students at SMP Negeri 1 Maiwa Regency of Enrekang Patent, and the samples were gathered from 28 of these students as well as Clu sampling. I'm sampling, says Ister Rando.In this study, there are 2 variables: the first is the independent variable, or the effect of using Capcuit media (x), and the second is the dependent variable, or the outcomes of scientific learning in class VII 3 students (y). The SMP Negeri 1 Maiwa Kabu i Patent Enrekang served as the research site for this project. The Muis Mean Rule was used to analyse the data after it had been obtained using the data collection technique of observation, tests, and documentation. Based on the analysis of the data, a value of X = 84.07 and a value of Y = 76.14 are obtained, allowing it to be observed that the usage of Capcut media has an impact on the outcomes of scientific learning for class VII students at SMP Negeri 1 Maiwa Kabu i Enrekang patent. According to the study's findings, class VII students at SMP Negeri 1 Maiwa, Kabu, and Patent Enrekang were influenced by their use of Capcut media in their science learning. This shows that the working hypothesis, according to which the usage of Capcuit media has an impact on the scientific learning outcomes of class VII students at SMP Negeri 1 Maiwa, is accepted.